Course and Predictors of Visual Outcome of Idiopathic Intracranial Hypertension. (4th March 2022) - Behbehani, Raed; Ali, Abdullah; Al-Moosa, Ashraf
ABSTRACT: Idiopathic intracranial hypertension (IIH) is a clinical syndrome characterised by headache and papilloedema that can lead to significant visual morbidity. There are few studies in the literature about the visual outcome of IIH. We have reviewed the record of 76 patients with IIH according to the modified Dandy criteria. There was a significant improvement in the Humphrey 24-2 mean deviation (MD) in the study eyes (worse affected eye at presentation) in both the medically treated group (+2.0 dB; from −5.60 dB at baseline to −3.60 dB at final follow-up, p < .01) and in the fellow eyes in the medically treated group (+1.70 dB, from −4.40 dB at baseline to −2.74 dB at final follow-up, p < .01). Higher papilloedema grade (beta −0.66, p < .001) and age ( p < .02) were inversely correlated with the final visual field MD in the study eye. The visual outcome for the IIH patients in our study was predominantly favourable, but patients with high-grade papilloedema had a worse visual prognosis and required more aggressive treatment.